Analisis Biaya Peremajaan Kebun Kelapa Sawit Rakyat (Studi Kasus KUD Sawit Kita Desa Lampisi Kecamatan Renah Mendaluh Kabupaten Tanjung Jabung Barat) - Purnamawati, Dyah; Ernawati, Ernawati; Napitupulu, Dompak MT (Jurnal MeA (Media Agribisnis), 2025)
The cost of rejuvenating smallholder palm oil in the funding framework of the Badan Pengelola Dana Perkebunan Kelapa Sawit (BPDPKS) is currently IDR 30 million per hectare/planter, which is still less than what is needed. The objectives of this research are 1. To describe the activities of Rejuvenating People's Palm Oil Plantations in KUD Sawit Kita, 2. Identifying the components of utilization of costs for Rejuvenating People's Oil Palm Plantations in KUD Sawit Kita, 3. Analyzing and evaluating the efficiency of utilizing costs for Rejuvenating People's Oil Palm Plantations in KUD Sawit We, and 4. Formulate detailed costs for efficient rejuvenation of people's oil palm plantations for our palm oil cooperatives.  The research method uses qualitative and quantitative descriptive analysis. KUD Sawit Kita, founded in 1991, was the first institution to receive PSR fees within the BPDPKS framework in West Tanjung Jabung Regency. Activities for Rejuvenating People's Palm Oil Plantations in KUD Sawit Kita P0-P3 include clearing land, providing ready-to-plant seeds, providing basic fertilizer, building and planting ground cover crops, providing P1-P3 fertilizer, controlling pests and diseases, building and rehabilitating Soil Conservation Buildings and Water, infrastructure rehabilitation, and monitoring. Based on the research results, it was found that the costs for rejuvenating people's oil palm plantations in KUD Sawit Kita were sourced from BPDPKS and independent smallholders. Based on the Efficiency Benchmark (ETU) P0-P3 value of 0.554, the Community Oil Palm Plantation Rejuvenation activity in KUD Sawit Kita is efficient but technically the work is considered not. The formulation of costs for rejuvenating people's oil palm plantations in KUD Sawit. We ideally follow the technical recommendations of Good Agriculture Practice (GAP) which is IDR. 55,181,551,-/Ha. So the current costs for rejuvenating people's oil palm plantations, which are channeled through BPDPKS, are indeed not enough.